THEORIES OF CHANGE IN THE PROCESS OF RURAL TRANSFORMATION: A REFINED WAY FORWARD - Rengarajan, V.; Sivasubramaniyan, K. (International Journal of Research -GRANTHAALAYAH, 2020)
Theory of change has been a useful evaluation tool for social science research. The interest in its use has been notable in recent years amongst international aid organisations and public authorities who make huge investment in social oriented intervention with more focus on the challenges related to gender empowerment and poverty cure in rural area. Logically, the achievement of intended change (impact) matters. In this context, the emerging question is: ’How are we getting a candid profile of change after the project implementation? The sources of data for analysis are taken from evaluation reports of Programme Evaluation Organisation, Planning Commission, Government of India. Among the convolutions, found in the theory of change the important one is that the monitoring system does not extend beyond output level in the causal path revealing only impaired impact confining to the physical achievement vs target. This apart, there is no process monitoring of implementation and mid-course corrections. The paper suggests a slew of critical constituents for the refined theory of change which include: (a) process monitoring; (b) result based monitoring and evaluation (c) transparent outcome and the impact; and (d) human behaviour.